Simultaneous Determination of Seven Carbohydrates in Tobacco by Ultrasonic Extraction-Ion Chromatography - Zhao, Yu; Guo, Bin; Liu, Jinyun; Yang, Huawu; Yin, Xinqiang; Tuo, Suxing; Zhang, Qiugen (Asian Journal of Chemistry, 2014)
A simple and reproducible method has been developed for the detection the carbohydrates of cigarettes. In this method, carbohydrates are obtained by ultrasonic extraction. The extracts are then analyzed using high-performance anion exchange chromatography followed by pulsed amperometric detection. The relative amounts of rhamnose, arabinose, fructose, glucose, xylose, maltose and sucrose, in cigarette are used for their characterization. The HPAEC-PAD method provided high selectivity, demonstrated good precision and had a large dynamic range in tobacco extracts.